DEVELOPING ENGLISH TEACHING MEDIA BY USING HOPSCOTCH TO TEACH SPEAKING TO STUDENTS OF PUBLIC JUNIOR HIGH SCHOOL - Hamdan; Fadli, Ahmad; Marita, Yosi; Hidayat, Ade (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted to develop English teaching media by using hopscotch to teach speaking to Students of Public Junior High School Tugumulyo. The problems of the study were: (1) How English teaching media by using hopscotch is developed to teach speaking at Students of Public Junior High School Tugumulyo? (2) How effective is English teaching media by using hopscotch to teach speaking at Students of Public Junior High School Tugumulyo? The objectives of the study were: (1) To describe how English teaching media by using hopscotch is developed to teach speaking at Students of Public Junior High School Tugumulyo. (2) To describe the effectiveness of using hopscotch to teach speaking at Students of Public Junior High School Tugumulyo. The author conducted the study through research and development (R&D) as the method of the study which developed products and measured the effectiveness of the development proposed by Borg and Gall (2007). The results of the study showed that English teaching media by using hopscotch was effective and appropriate to teach speaking to junior high school students. It was supported by the results of the independent sample t-test showed the value of t-obtained was -10.422. At the significance level p< 0.05 for the two-tailed testing with the degree of freedom 27. The critical value of the t-table was 2.052. It can be said that there was significantly different and influential between pre and post-test. Therefore, hopscotch was effective for learning English and it can be applied in the teaching and learning process at Junior High School.